2019
DOI: 10.1111/jsr.12895
|View full text |Cite
|
Sign up to set email alerts
|

Unique sleep‐stage transitions determined by obstructive sleep apnea severity, age and gender

Abstract: Summary In obstructive sleep apnea, patients’ sleep is fragmented leading to excessive daytime sleepiness and co‐morbidities like arterial hypertension. However, traditional metrics are not always directly correlated with daytime sleepiness, and the association between traditional sleep quality metrics like sleep duration and arterial hypertension is still ambiguous. In a development cohort, we analysed hypnograms from mild (n = 209), moderate (n = 222) and severe (n = 272) obstructive sleep apnea patients as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
(62 reference statements)
0
9
1
Order By: Relevance
“…GERD-Q consists of six questions: heartburn, reflux, epigastric pain, nausea, sleep disorder, and anti- Third, previous studies have found a sex difference in the incidence of OSA. 47,48 However, sex did not affect the therapeutic effect of cough in patients with OSA and concomitant GER in present study. It suggested that sex could affect the incidence of OSA, but CPAP therapy was equally important for cough in male and female patients with OSA and concomitant GER.…”
Section: Discussioncontrasting
confidence: 65%
“…GERD-Q consists of six questions: heartburn, reflux, epigastric pain, nausea, sleep disorder, and anti- Third, previous studies have found a sex difference in the incidence of OSA. 47,48 However, sex did not affect the therapeutic effect of cough in patients with OSA and concomitant GER in present study. It suggested that sex could affect the incidence of OSA, but CPAP therapy was equally important for cough in male and female patients with OSA and concomitant GER.…”
Section: Discussioncontrasting
confidence: 65%
“…In this review, the studies represented 28 countries including Argentina, Australia, Belgium, Brazil, Bulgaria, Cameroon, China, Czech Republic, Finland, France, Germany, Greece, India, Iran, Italy, Ireland, Japan, Korea, Lebanon, New Zealand, Poland, Romania, Spain, Saudi Arabia, Slovakia, Taiwan, Turkey, and the United States. A multicenter study, conducted by Wächter et al, 2020 [ 51 ], represented 11 sleep centers in 8 European countries.…”
Section: Resultsmentioning
confidence: 99%
“…Another cross-sectional study involving 2740 adults in Korea [ 50 ] identified the “high risk” individuals as being older aged and having a BMI ≥ 25 kg/m 2 for OSA. Several other studies that involved large samples included a cross-sectional study ( n = 2208) in Japan addressing the association between hypertension and OSA [ 42 ], a multicenter study ( n = 1877) in Europe looking for the effects of OSA severity and other comorbidities on sleep pattern [ 51 ], a prospective cohort study ( n = 1825) in Korea determining the association between hypertension with OSA in patients with high levels of homocysteine in the blood [ 36 ], and a cross-sectional study ( n = 1272) in Belgium determining the prevalence of hypertension with insomnia [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The associate editor coordinating the review of this manuscript and approving it for publication was Rajeeb Dey . but has persisted for less than three months, it is considered short-term insomnia [3]. To diagnose insomnia, the physician may first execute a physical exam to look for signs of medical problems that may be related to insomnia and ask some sleep-related questions, such as sleep-wake pattern and daytime sleepiness.…”
Section: Introductionmentioning
confidence: 99%